ENHANCING ROUTINE SCREENING AND CARE LINKAGE FOR HEPATITIS C VIRUS IN AN URBAN SAFETY-NET HEALTH SYSTEM - Mohammed Abdullah Morshed Alfawzan1, Ahmad Abdulaziz Fahad Alassaf2, Mansour Mohammed Ibrahim Altamimi3, Hussain Ali Khulaif Alharbi4, ,; Nasser Saud Nasser Alshammari5, Farhan Mansour Farhan Aldghmani6, Farhan Khalaf Munahi Alunazi7, (Chelonian Research Foundation, 2022)
Objective: Hepatitis C virus (HCV) remains a significant public health concern globally. This study aims to evaluate an HCV screening and linkage-to-care program within an urban safety-net health system. Methods: The program, implemented universal HCV screening across emergency department, inpatient, and outpatient settings, coupled with patient navigation services for positive cases. Data were collected , including patient demographics, risk factors, and outcomes such as screening numbers, test results, new diagnoses, navigation eligibility, and appointment attendance rates. Outcomes were also assessed based on patient knowledge of their infection. Results: Among 21,018 individuals screened, 6% (1318/21,018) tested positive for HCV antibody, with 68% (878/1293) confirming positive HCV RNA results. Demographically, 68% were born between 1945-1965, 68% were male, and 65% were Black. Of those diagnosed, 55% were new cases, with risk factors including drug use (53%), unemployment (30%), and prior incarceration (21%). Among navigation-eligible patients (64%), 50% accessed imaging services, and 72% attended their initial medical appointment post-imaging. Conclusion: Patient navigation significantly contributed to successful care linkage, yet ongoing financial sustainability for navigation services remains a challenge. Keywords: hepatitis C, patient navigation, universal screening